Influence of kinetic parameters and diffusion coefficients on stationary concentration of electroactive and electroinactive species in a model electrochemical process with a preceding chemical reaction - O. I. Gichan (Хімія, фізика та технологія поверхні)
This work is aimed at studying the influence of kinetic parameters and diffusion coefficients on stationary concentration distribution of electroactive and electroinactive species in a model electrochemical process with a preceding chemical reaction under constant current. We consider a preceding homogeneous first-order chemical reaction with a reversible heterogeneous electrochemical reaction at a planar electrode surface. To elucidate the peculiarities of stationary concentration distribution of electroactive and electroinactive species in a thin stagnant layer attached to a planar electrode surface, the exact solutions of a system of differential equations describing the variations of the concentrations of the participating species with a distance to electrode surface have been analyzed. The cases of equal and unequal diffusion coefficients of species involved in a preceding chemical reaction have been considered. It has been shown that the diffusion coefficients of both reacting species can affect their concentration profiles in a thin stagnant layer attached to electrode surface. The calculations demonstrate that the stationary concentration of electroactive and electroinactive species decreases with an increase of the diffusion coefficients. The influence of the rate constants of a preceding chemical reaction on the stationary concentration is different for electroactive species and electroinactive one. As the rate constants of a preceding chemical reaction are increased, the stationary concentration of electroactive species decreases, whereas the stationary concentration of electroinactive species increases slightly. This is also valid for the case of the stationary surface concentration of electroactive and electroinactive species. The thickness of a thin stagnant layer attached to a planar electrode surface where a change of the concentration of electroactive species takes place, also affects the stationary concentration distributions. The effect of this parameter is especially crucial at low values of a preceding chemical reaction rate constants.